2002
DOI: 10.1148/radiol.2223010558
|View full text |Cite
|
Sign up to set email alerts
|

High-Grade Gliomas and Solitary Metastases: Differentiation by Using Perfusion and Proton Spectroscopic MR Imaging

Abstract: Although conventional MR imaging characteristics of solitary metastases and primary high-grade gliomas may sometimes be similar, perfusion-weighted and spectroscopic MR imaging enable distinction between the two.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
357
6
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 510 publications
(405 citation statements)
references
References 16 publications
36
357
6
6
Order By: Relevance
“…Small studies have suggested that other tests such as dynamic contrast-enhanced MRI, perfusion imaging, and magnetic resonance spectroscopy may help differentiate between brain metastases and high-grade gliomas. 15,16 The bulk of the literature regarding the use of brain CT or MRI for staging purposes has dealt with lung cancer. Nevertheless, there is still no general agreement on when to use CT or MRI as part of the initial staging evaluation for a patient newly diagnosed with lung cancer.…”
Section: Ct/mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Small studies have suggested that other tests such as dynamic contrast-enhanced MRI, perfusion imaging, and magnetic resonance spectroscopy may help differentiate between brain metastases and high-grade gliomas. 15,16 The bulk of the literature regarding the use of brain CT or MRI for staging purposes has dealt with lung cancer. Nevertheless, there is still no general agreement on when to use CT or MRI as part of the initial staging evaluation for a patient newly diagnosed with lung cancer.…”
Section: Ct/mrimentioning
confidence: 99%
“…25 However, new MRI methods (perfusion and magnetic resonance spectroscopy) have shown improvement in specificity. 15,16 Identification of a solitary brain lesion in a patient with a controlled extracranial primary cancer with no other sites of disease on systemic evaluation should be followed by MRI with increased dose of contrast and, if no additional lesions are identified, histologic verification. In patients found to have multiple brain lesions with imaging characteristics compatible with metastases, the decision whether to pursue histologic confirmation is based on the clinical picture.…”
Section: Pathologic Confirmationmentioning
confidence: 99%
“…Mucinous metastases tend to show T2 hypointensity, especially metastatic colon adenocarcinoma. Calcification typically occurs in lung or breast tumors (1,(3)(4)(5)19,28). Cystic lesions are associated with metastatic squamous cell carcinoma.…”
Section: Review Of Selected Additional Tumorsmentioning
confidence: 99%
“…In this situation, evaluation of the peritumoral region of T2 hyperintensity can be extremely helpful (19). The peritumoral region of metastases represents vasogenic edema caused by increased interstitial water (60), in contrast to the peritumoral region of gliomas, which consists of tumoral infiltration into the brain parenchyma and accompanying neovascularity beyond the contrast-enhancing margins of the tumor (30).…”
Section: Peritumoralmentioning
confidence: 99%
See 1 more Smart Citation